PEMETAAN GERAKAN POLITIK ISLAM RADIKAL DI PANTURA JAWA TIMUR - Nurhayati, Aniek (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This study explores the mapping of radical Islamic movements in the northern coasts of East Java. Based on field research and using qualitative approach, this study aims to answer the questionson democracy, Islamic state, the implementation of Islamic law (shari’ah), and women’s leadership. The study indicates that HTI, MMI and a number of Islamic boarding schools consider democracy irreconcilable with Islam. However, LDII asserts that democracy is a good system. To HTI, MMI and several Islamic boarding schoolsthe establishment of Islamic state in Indonesia is their desired main goal. In addition, HTI, MMI, and some Islamic boarding schools require firm implementation of the Islamic law, while to LDII Islamic law is a personal duty of every Muslim without any requirement of establishing an Islamic state. Finally, HTI, MMI, and several Islamic boarding schools firmlyrefused women’s leadership as apresident. Interestingly, LDII states the possibility of women to be a president.